Contextual awareness, response and evaluation (CARE) of diabetes in poor urban communities in Ghana: the CARE diabetes project qualitative study protocol - Leonard Baatiema; Daniel Llywelyn Strachan; Lydia Osetohamhen Okoibhole; Irene Akwo Kretchy; Mawuli Kushitor; Raphael Baffour Awuah; Olutobi Adekunle Sanuade; Ernestina Korleki Danyki; Samuel Amon; Kafui Adjaye-Gbewonyo; Haim Yacobi; Megan Vaughan; et al. (Taylor & Francis Group, 2024)
Diabetes remains a major, global clinical and public health threat with consistent rises in prevalence around the world over the past four decades. Two-thirds of the projected increases in global diabetes prevalence to 2045 are expected to come from low- and middle-income countries, including those in sub-Saharan Africa. Ghana is typical of this trend. However, there are gaps in evidence regarding the appropriate development of interventions and well-targeted policies for diabetes prevention and treatment that pay due attention to relevant local conditions and influences. Due consideration to community perspectives of environmental influences on the causes of diabetes, access to appropriate health services and care seeking for diabetes prevention and management is warranted, especially in urban settings. The 'Contextual Awareness, Response and Evaluation (CARE): Diabetes in Ghana' project is a mixed methods study in Ga Mashie, Accra. An epidemiological survey is described elsewhere. Six qualitative studies utilising a range of methodologies are proposed in this protocol to generate a contextual understanding of type 2 diabetes mellitus in an urban poor population. They focus on community, care provider, and policy stakeholder perspectives with a focus on food markets and environmental influences, the demand and supply of health services, and the history of the Ga Mashie community and its inhabitants. The results will be shared with the community in Ga Mashie and with health policy stakeholders in Ghana and other settings where the findings may be usefully transferable for the development of community-based interventions for diabetes prevention and control.